2016
DOI: 10.4236/ajibm.2016.63024
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Job Satisfaction: Implications for Leaders of Accountants

Abstract: This study conducted a review of the meta-analytic literature which correlated leadership and job satisfaction. Twenty-five meta-analytic correlations were extracted and analyzed in order to focus specifically on how leadership affected worker job satisfaction. Results indicated that charismatic and transformational leadership behaviors had the highest positive correlations with worker job satisfaction while non-contingent punishment and abusive supervision showed low negative relationships to worker job satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…If the leader is close to employees, respect to the employees opinion and to communicate openly would increase job satisfaction. Some previous research found the influence of leadership style and organizational commitment to job satisfaction and ultimately led to the turnover intention (Fitriany et al, 2011;Joo & Ready, 2012;Mehrad & Fallahi, 2014;Long et al, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Sun et al, 2016). Based on the basis of previous studies review and explanations described earlier, the fourt Hypothesis proposed in this study is: H4: Leadership Style has positive effect on Job Satisfaction.…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 66%
See 3 more Smart Citations
“…If the leader is close to employees, respect to the employees opinion and to communicate openly would increase job satisfaction. Some previous research found the influence of leadership style and organizational commitment to job satisfaction and ultimately led to the turnover intention (Fitriany et al, 2011;Joo & Ready, 2012;Mehrad & Fallahi, 2014;Long et al, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Sun et al, 2016). Based on the basis of previous studies review and explanations described earlier, the fourt Hypothesis proposed in this study is: H4: Leadership Style has positive effect on Job Satisfaction.…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 66%
“…This finding shows that if employees felt comfortable with his supervisor's leadership style applied will influence in the increase of job satisfaction (Fitriany et al, 2011;Joo & Ready, 2012;Mehrad & Fallahi, 2014;Long et al, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Sun et al, 2016).…”
Section: Regression Analysismentioning
confidence: 91%
See 2 more Smart Citations
“…However, the conduct of the process has not lived up to the required level, since independence and to this day, these institutions knew many conventions in the search for efficiency. It is interesting Algerian institutions attracting talent and maintains regarded as an investment in their greatest resource and human capital to keep pace with changes economic developments [6][7][8][9].…”
Section: Importance Of the Studymentioning
confidence: 99%